The Meanings of Autonomy: Brazilian and Mexican Reactions to Tensions between China and the United States - Élodie Brun; Ana Covarrubias (Revista Brasileira de Política Internacional)
Abstract The article addresses the question of autonomy in Mexico’s and Brazil’s foreign policies in the context of increasing tensions between the United States and China. Although Mexico’s and Brazil’s relations with China —and to a lesser extent the United States— are very different in nature, both Latin American countries face the same challenge of finding a balance in relations with both great powers. The article analyzes Mexico’s and Brazil’s handling of a “triangular relationship” since 2018, illustrating the scope and limits of each country’s autonomy. In the case of Mexico, economic integration with the United States explains the place of China as both an opportunity and a threat; in the case of Brazil, although China is its major trade partner, domestic interests become as important as structural elements, and its government cannot disregard US concerns. In addition to the review of secondary literature, the article uses a series of interviews of Mexican and Brazilian diplomats.